A model of the glacial retreat of upper Rennick Glacier, Victoria Land, Antarctica - Giuseppe Orombelli; Maria Cristina Salvatore; Mirco Meneghel; Aldino Bondesan (Annals of Glaciology, 1999)
AbstractThe morphology of the Lichen Hills in the upper section of Rennick Glacier, Victoria Land, Antarctica, is summarised as follows: (a) a top surface on the volcanic rocks with scattered erratic blocks; (b) an exhumed Kukri Peneplain, sculptured with roches moutonnees with striae and crescentic gouges on which lie moraines and patches of drift of mainly volcanic rocks; (c) a granitic bedrock eroded by glaciers into sharp peaks and cirques on top of which there is a glacial drift attributable to ancient blue-ice areas higher than those observed at present and which may be correlated with the Terra Nova drift (Late Wisconsin); (d) various Holocene ice-cored moraines that are pushed to the lee side of the nunataks arid are often banded in strips of different lithology. The bands of the Holocene moraines are related to the rock complexes that became exposed from the ice during the lowering of the surface of the glacier Analysis of the lithology and pattern of the supraglacial debris, as well as of the blue-ice areas, allows us to construct a depositional model for the moraines, and to relate the glacial drift to blue-ice areas existing since the Last Glacial Maximum (LGM).The proposed model shows the different stages of recession of upper Rennick Glacier that are also valid for similar situations observed in northern Victoria Land. A surface lowering of upper Rennick Glacier of several hundred metres shows that significant changes have occurred at the Pacific edge of the East Antarctic ice sheet since the LGM.